Object-oriented model of a formal description of an information and communication system - Poddubnyi, V.O.; Gvozdov, R.Y.; Sievierinov, О.V.; Fedorchenko, V.M. (Radiotekhnika, 2022)
The purpose of the article is to study algorithms for the formal description of information and communication systems. The article discusses the main provisions on the formal representation of objects of information and communication systems. It is noted that the main environments of the information and communication system that are subject to a formal description are: physical environment, computing system environment, user environment, information environment. These components of the information and communication system are considered in detail, analyzed and documented in an informal form (in the form of text). There is a need for a mechanism for a unified description of a system that includes all environments. Such a description will be unambiguously formalized with well-defined mathematical concepts. The mechanism of a single formal description or the technique of a formal description will be unambiguous in understanding and serve as a control description when developing an information security policy in an information and communication system. An algorithm for the formal description of the information and communication system is proposed. In this algorithm, it is proposed to focus on the types and interaction of objects with each other. In such a scheme, attention is focused on such concepts as the object, the characteristics of the object, and the type of interaction with the object. Further consideration of the created block diagrams (graphs) is proposed to explore the possibilities of using this model to simulate cyber-attacks. Since each element contains fields that connect it to other elements, and each attack has an "entry point" using graph theory, it is possible to traverse the graph to determine the possible horizontal propagation paths of a cyber-attack.